Knowing God, knowing emptiness: an epistemological exploration of Bernard Lonergan, Karl Rahner and Nāgārjuna - Robinson, John N. C. (Equinox, 2022)
"Knowing God, Knowing Emptiness examines the viability of the epistemology proposed by Bernard Lonergan in his seminal work Insight, particularly with regard to its possible application in the field of interreligious dialogue. It applies Lonergan's epistemological categories to Karl Rahner's Foundations of Christian Faith, and Nāgārjuna's Mūlamadhyamakakārikā"--